2015
DOI: 10.1093/gastro/gov042
|View full text |Cite
|
Sign up to set email alerts
|

Extra-hepatic manifestations associated with hepatitis E virus infection: a comprehensive review of the literature

Abstract: Background and aims: Hepatitis E virus (HEV) infection is a significant public health problem that afflicts almost 20 million individuals annually and causes acute liver injury in 3.5 million, with approximately 56 000 deaths. As with other viral hepatitides, extra-hepatic manifestations could represent an important aspect of this infection. The spectrum of these manifestations is still emerging. Acute pancreatitis and neurological, musculoskeletal, hematological, renal, and other immune-mediated manifestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
132
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(138 citation statements)
references
References 126 publications
(78 reference statements)
1
132
0
5
Order By: Relevance
“…Some of these extrahepatic manifestations seem to be restricted to specific HEV-genotypes. For instance, more than 50 cases of HEV-related courses of acute pancreatitis have been reported and all cases occurred in areas endemic for HEV GT 1 [62], while renal manifestations were predominantly reported in HEV GT 3 infections [63]. Extrahepatic manifestations of HEV-infection will be discussed in detail in a separate article of this issue.…”
Section: Tropical and Autochthonous Hev Infections May Lead To Difmentioning
confidence: 99%
“…Some of these extrahepatic manifestations seem to be restricted to specific HEV-genotypes. For instance, more than 50 cases of HEV-related courses of acute pancreatitis have been reported and all cases occurred in areas endemic for HEV GT 1 [62], while renal manifestations were predominantly reported in HEV GT 3 infections [63]. Extrahepatic manifestations of HEV-infection will be discussed in detail in a separate article of this issue.…”
Section: Tropical and Autochthonous Hev Infections May Lead To Difmentioning
confidence: 99%
“…Glutathione levels are already low in red blood cells of G6PD deficient subjects, however, and the further reduction due to viral hepatitis precipitates severe hemolysis 6,7. A recent review of all such cases reported to date suggested that renal failure occurs in the setting of high bilirubin levels, but the exact cause remained undetermined 8. It has been proposed that acute tubular necrosis and mechanical tubular obstruction due to hematin and bilirubin may contribute 7.…”
Section: Discussionmentioning
confidence: 99%
“…Till date hardly more than 30 to 50 cases of acute pancreatitis due to hepatitis E have been reported, out of which the largest series of 16 patients was reported from SGPGI, Lucknow. 5 Apart from pancreatitis, HEV can also cause extra-hepatic manifestations 6 such as neurological symptom, kidney injury, haematological manifestation, etc. Most cases of Acute Pancreatitis associated with infection with hepatotropic viruses have been reported in the setting of ALF.…”
Section: Discussionmentioning
confidence: 99%